2019
DOI: 10.1039/c9py00672a
|View full text |Cite
|
Sign up to set email alerts
|

Acyloxyimide derivatives as efficient promoters of polyolefin C–H functionalization: application in the melt grafting of maleic anhydride onto polyethylene

Abstract: Acyloxyimides as a new H-abstracting agent have been developed for the radical grafting of maleic anhydride (MA) onto polyethylene in the melt state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…Similarly, Gigmes and co-workers recently reported near stoichiometric acetic acid generation when N-acetyloxy phthalimide, which is also thought undergo N-O homolysis, 17 was utilized for polyethylene grafting and functionalization. 32 These results are clearly indicative of successful escape of the caged carboxylate radical with little if any decarboxylation. Moreover, the precise fate of the aminyl radical fragment and its role in the controlled degradation process is also unclear.…”
Section: Scheme 3 N-o Vs C-o Cleavage In a Prototypical Nacyloxyamine (Tempo-ac) And An N-alkoxyamine (Tempo-sty)mentioning
confidence: 95%
See 1 more Smart Citation
“…Similarly, Gigmes and co-workers recently reported near stoichiometric acetic acid generation when N-acetyloxy phthalimide, which is also thought undergo N-O homolysis, 17 was utilized for polyethylene grafting and functionalization. 32 These results are clearly indicative of successful escape of the caged carboxylate radical with little if any decarboxylation. Moreover, the precise fate of the aminyl radical fragment and its role in the controlled degradation process is also unclear.…”
Section: Scheme 3 N-o Vs C-o Cleavage In a Prototypical Nacyloxyamine (Tempo-ac) And An N-alkoxyamine (Tempo-sty)mentioning
confidence: 95%
“…Intriguingly, in unpublished studies, we have observed nearly stoichiometric amounts of acetic acid when various N -acyloxyamines were decomposed in the presence of PP. Similarly, Gigmes and co-workers recently reported near stoichiometric acetic acid generation when N -acetyloxy phthalimide, which is also thought to undergo N–O homolysis, was utilized for polyethylene grafting and functionalization . These results are clearly indicative of successful escape of the caged carboxylate radical with little if any decarboxylation.…”
Section: Introductionmentioning
confidence: 99%
“…Polyolefins are a predominant class of polymer used globally, with polyethylene (PE) used in a remarkably wide range of applications due to its high thermal/chemical stability, ease of processing, and favorable mechanical properties. As such, there is substantial interest in the development and production of functionalized PE, whether by incorporation of reactive groups during polymerization, postpolymerization modification, or some combination of the two. One such strategy is ring-opening metathesis polymerization (ROMP) of cyclic olefins to give polyalkenamers that can be hydrogenated to yield the corresponding polyolefins; the inclusion of a difunctional acyclic alkene as chain-transfer agent (CTA) produces telechelic polyolefins containing the corresponding end groups. The utility of CTAs with varied functionality has been demonstrated in numerous examples, ,− with the primary requirement being the mutual compatibility of the CTA and the polymerization catalyst, typically ruthenium-based metal carbene derivatives.…”
mentioning
confidence: 99%
“…For example, the in situ melt polymerization− transesterification (Route B) is very similar to the industrial melt-processes for grafting maleic anhydride to polyolefins. 29 In addition, the reaction temperature for transesterifications (160 °C) is close to the typical melt processing temperatures for PLA (160−200 °C). 30 We note that attempts to implement the direct transesterification between salicylic acid and PLA resulted in significant PLA degradation.…”
Section: ■ Results and Discussionmentioning
confidence: 59%
“…Transesterification in the melt state showed comparable extent of reaction to that in solution but at shorter reaction times (3 h), bolstering the potential of this approach in practical scenarios. For example, the in situ melt polymerization–transesterification (Route B) is very similar to the industrial melt-processes for grafting maleic anhydride to polyolefins . In addition, the reaction temperature for transesterifications (160 °C) is close to the typical melt processing temperatures for PLA (160–200 °C) .…”
Section: Resultsmentioning
confidence: 85%